2021
DOI: 10.1016/j.jbi.2021.103887
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of stacking based ARIMA model for prediction of Covid-19 cases in India

Abstract: Background Time-series forecasting has a critical role during pandemics as it provides essential information that can lead to abstaining from the spread of the disease. The novel coronavirus disease, COVID-19, is spreading rapidly all over the world. The countries with dense populations, in particular, such as India, await imminent risk in tackling the epidemic. Different forecasting models are being used to predict future cases of COVID-19. The predicament for most of them is that they are not ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 62 publications
0
29
0
1
Order By: Relevance
“…Swaraj et al developed a model integrating ARIMA and nonlinear autoregressive neural network (NAR) for predicting the COVID-19 outbreak in India. The result shows a significant reduction in evaluation metrics (RMSE: 16.23%, MAE: 37.89% and MAPE: 39.53%) with the hybrid model compared to the single ARIMA model [ 19 ]. Besides, Wadhwa et al studied the effects of lockdown policy on disease transmission by predicting the number of active cases all over India.…”
Section: Related Workmentioning
confidence: 99%
“…Swaraj et al developed a model integrating ARIMA and nonlinear autoregressive neural network (NAR) for predicting the COVID-19 outbreak in India. The result shows a significant reduction in evaluation metrics (RMSE: 16.23%, MAE: 37.89% and MAPE: 39.53%) with the hybrid model compared to the single ARIMA model [ 19 ]. Besides, Wadhwa et al studied the effects of lockdown policy on disease transmission by predicting the number of active cases all over India.…”
Section: Related Workmentioning
confidence: 99%
“…Methods for short-term forecasting are usually data-driven, but they can also incorporate domain knowledge in the form of compartmental modelling (i.e., SIR-type models – see [48] ), as a means of integrating and simultaneously forecasting in a coherent manner multiple epidemiological indicators, such as cases, hospitalizations, and deaths. The study by Swaraj et al [21] uses a statistical data-driven approach, Aljaaf et al [22] , Dairi et al [23] , and Safari et al [24] use a machine learning data-driven approach, while Jing et al [25] uses compartmental modelling. Most of the forecasting studies were conducted as stand-alone evaluations or comparisons of methods by researchers who were not directly affiliated with public health authorities mandated to perform surveillance.…”
Section: Forecasting and Epidemic Modelingmentioning
confidence: 99%
“…Most of the forecasting studies were conducted as stand-alone evaluations or comparisons of methods by researchers who were not directly affiliated with public health authorities mandated to perform surveillance. In terms of epidemiological indicators being forecast, the studies focused on confirmed cases, hospitalizations and deaths, although the contribution of smartphone mapping data, was explored by Jing et al [25] Methodologically, most studies used statistical and ML methods, either in comparison (Dairi et al [23] and Safari et al [24] ), within an ensemble (Aljaaf et al [22] and Swaraj et al [21] ), or as a part of a pipeline. Although results varied, findings were consistent with a recent review of methods for aberration detection in public health, with ML methods tending to outperform statistical methods for short-term forecasting.…”
Section: Forecasting and Epidemic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to effective forecasting models for other epidemics, Hernandez-Matamoros [ 18 ] assessed the autoregressive integrated moving average (ARIMA) model for 145 countries in six regions, and this turned out to be also effective for COVID-19. Swaraj [ 19 ] proposed an ARIMA-based model that could capture the linear and non-linear components of the data by integrating an autoregressive neural network (NAR). Machine-learning and deep-learning models have also shown outstanding ability to forecast from time-series data, especially Long Short-Term Memory (LSTM), due to their capability to unveil dependencies over a long distance in time.…”
Section: Introductionmentioning
confidence: 99%